Diatomeas (Bacillariophyceae) subfósiles del Brazo Blest del Lago Nahuel Huapi, Argentina - García, María Luján (2015)
Subfossil diatoms from Lago Nahuel Huapi (Brazo Blest), Argentina. The main objective of this study was to analyze subfossil diatoms from Nahuel Huapi Lake (Brazo Blest) in order to increase the knowledge about the region’s phycoflora, which until nowadays has been poorly studied. There were 47 genera and 114 infrageneric taxa recorded, from which 1 is recorded for first time for Argentina and 18 are new records for Northern Patagonia (Argentina).